Attachment, Intellectual Disabilities and Mental Health: Research, Assessment and Intervention. Issue 1 (18th December 2012) - Schuengel, Carlo; de, Johanna Clasien; Sterkenburg, Paula S.; Kef, Sabina
<x xml:space="preserve">Abstract</x> Background Attachment theory is highly influential in child and adult mental health research and practice. Research and practice have started now to explore the potential value of an attachment perspective for understanding and alleviating the challenges that persons with intellectual disabilities face in mental health and social participation. Materials and Methods Research on attachment and intellectual disabilities is reviewed on its importance for knowledge, assessment and intervention. Results Progress was found in understanding and distinguishing attachment behaviours, attachment relationships, attachment representations, attachment styles and attachment disorders and their respective implications for assessment and intervention. Conclusions Of the various attachment‐related concepts, insights into attachment behaviours and relationships showed the most promise for practical applications in the field of intellectual disabilities. Findings on representations, styles and disorders were inconclusive or preliminary. Attachment‐informed research and practice can be part of emerging developmental understanding of functioning with intellectual disabilities.